The Location of High Knowledge Content Activities in the Canadian Urban System, 1971-1991 - Bataïni, Sophie-Hélène; Coffey, William (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1998)
It is widely recognized that certain activities have a higher capacity than others topromote economic growth and development. Many of these more dynamic activities areoften said to involve “high technology”. In this paper we first question the conceptualand operational utility of the notion “high technology”. We then propose a morestraightforward and more easily measured concept —high knowledge content—,demonstrating that activities of this nature may be found in “low tech” sectors. By means of an empirical analysis, we then attempt to contribute to a better understanding of the locational dynamics of high knowledge content activities within the Canadian urban system over the period 1971-1991. Specifically, we seek to determine if this class of activities is becoming spatially more concentrated or more dispersed across the urban system. The answer to this question is particularly important for smaller communities in peripheral regions whose economic bases are highly dependent upon “low tech” activities.